Adab of Learning in Kitāb al-ʿIlm of Ṣaḥīḥ al-Bukhārī: A Ḥadīth-Based Conceptual Model for Islamic Education - Silaturahim, Rahmat; Nasution, Syamruddin; Zarkasih (LETIGES, 2025)
This study aims to clarify the concept of adab in Islamic learning by developing a structured conceptual model grounded in Kitāb al-ʿIlm of Ṣaḥīḥ al-Bukhārī. While existing scholarship has widely discussed adab within Islamic education, its components are often presented in a fragmented and normative manner, resulting in limited conceptual organisation for contemporary Islamic Education. Addressing this gap, the article conceptualises adab as an integrative moral–epistemic framework that connects classical Islamic sources with modern educational theory. Methodologically, the study employs a qualitative conceptual design using an integrative literature review combined with directed content analysis. The data consist of selected ḥadīth from Kitāb al-ʿIlm of Ṣaḥīḥ al-Bukhārī as the primary textual source, supplemented by authoritative classical commentaries. Data were collected through systematic identification and thematic extraction of adab-related materials and analysed by organising concepts into predefined analytical categories while allowing relevant themes to emerge. Analytical rigour was ensured through transparent source selection, consistent transliteration, and triangulation with classical interpretations. The analysis identifies three core dimensions of adab in learning: ethical relations between teachers and learners, the order and norms governing learning settings, and the ethics of inquiry, listening, referencing, and knowledge transmission. These dimensions operate alongside enabling conditions, namely intention, teacher exemplarity, and institutional culture, which together shape educational outcomes such as learner engagement, the quality of scholarly discourse, and the formation of a stable ethical disposition rooted in adab. The article further proposes four theory-driven propositions to guide future empirical research. As a text-based conceptual study, the model invites empirical testing across diverse educational contexts and contributes a transferable analytical framework for Islamic education research.